1967
DOI: 10.1111/j.1550-7408.1967.tb01991.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Antioxidants to Tetrahymena pyriformis*

Abstract: SYNOPSIS. The cytotoxicity of 97 antioxidants of various structural types was determined for Tetrahymena pyriformis grown in a peptone medium. Cytotoxicity fo Tetrahymena, generally, was positively associated with acute oral tomicoiciity to rats but not with antioxidant pdency as measured by the Tetrahymena photodynamic assay for antioxidants. Some commonly used hindered‐phenol, lipidsoluble anttioxidants, e.g., 2,6‐di‐tert.‐butyl‐P‐cresol (BHT), had low toxicity (to Tetrahymena but poor antioxidant activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The oral lethal dose (LD 50 ) of drometrizole in mice was reported to be 6.5 g/kg and > 5.0 g/kg by Labor Hygiene and Occupational Diseases (20) and Epstein et al . (21), respectively (20,21). Oral toxicity was evaluated in rats for nail care cosmetics containing 1%, 0.3% and 0.03% of drometrizole.…”
Section: Hazard Identificationmentioning
confidence: 99%
“…The oral lethal dose (LD 50 ) of drometrizole in mice was reported to be 6.5 g/kg and > 5.0 g/kg by Labor Hygiene and Occupational Diseases (20) and Epstein et al . (21), respectively (20,21). Oral toxicity was evaluated in rats for nail care cosmetics containing 1%, 0.3% and 0.03% of drometrizole.…”
Section: Hazard Identificationmentioning
confidence: 99%
“…Its use is subject to the limitations set forth in the Code of Federal Regulations (2003), Title 21, part 178.2010. Epstein et al (1965Epstein et al ( , 1967 reported that Drometrizole had very low cytotoxicity to Tetrahymena pyriformis, with a median LD 50 of 640 μg/ml.…”
Section: Noncosmeticmentioning
confidence: 99%
“…The acute oral LD 50 of Drometrizole in mice is given as 6.5 g/kg according to the Labor Hygiene and Occupational Diseases (1966), in the then Soviet Union, and >5.0 g/kg according to Epstein (1967). Komarova and Maksimova (1979) administered 5.0 and 10.0 g/kg Drometrizole, in sunflower oil, by stomach tube to white mice and rats.…”
Section: Acute Oral Toxicitymentioning
confidence: 99%
“…The majority of the studies on the toxicity of PNA used mammalian models, and the few data that exist on aquatic vertebrates were acute exposures. The EC 50 for cell proliferation was determined to be 2 mg/L for Tetrahymena pyriformis (ciliate) exposed to PNA for 48 h (Epstein et al 1967). The LC 50 was in the range of 0.44-0.74 mg/L for Oncorhynchus mykiss (rainbow trout) and 0.57-0.82 mg/L for Lepomis macrochirus (bluegill).…”
mentioning
confidence: 99%